Growth of Boron Nitride Nanotube Over Al‐Based Active Catalyst and its Application in Thermal Management. Issue 4 (4th January 2023) - He, Qian; Ding, Liping; Wu, Liyun; Zhou, Zhengyang; Wang, Ying; Xu, Tao; Wang, Nanyang; Zhang, Kai; Wang, Xuebin; Ding, Feng; Zhang, Jin; Yao, Yagang
Abstract : The effective identification of the active catalytic phase is essential to elucidate the growth mechanism of boron nitride nanotubes (BNNTs) and realize their controllable and scalable synthesis. However, owing to the complexity of chemical reactions during BNNT growth via chemical vapor deposition (CVD) and the lack of techniques for in situ characterization at high temperatures (1100–1300 °C), identifying the true catalyst during BNNT growth is challenging. Herein, an aluminum (Al)‐based active catalyst for BNNT growth via CVD is investigated. The initial Al2 O3 nanoparticle catalyst precursor is transformed into an Al‐B phase prior to BNNT growth. Based on our density functional theory‐based molecular dynamic simulations of BNNT nucleation, AlB x ( x  = 1.5 to 2) shows catalytic activity for the formation of BN chains and BN six‐membered rings. Confirmatory experiments demonstrate that AlB2 is the active Al‐based catalyst during BNNT growth. A nanocomposite is prepared from cellulose nanocrystal, and purified BNNTs exhibited a high in‐plane thermal conductivity of 13.33 W m −1  K −1 at 20 wt% BNNTs. A further application for light‐emitting diode chip cooling demonstrates excellent heat‐dissipation performance of the nanocomposite film. Thus, this study can guide the controllable synthesis of high‐quality BNNTs and facilitate their use in thermal interface materials. Abstract : AlB2 shows catalytic activity for the formation of BN chains and BN six‐membered rings, which are regarded as early indicators of BNNT growth. Confirmatory experiments further demonstrate that AlB2 is the active Al‐based catalyst during BNNT growth. The AlB2 particle itself can also decompose to produce component B and combine with the N atoms to form BN species.